Exploring the Applicability of the Science Communication Research Agenda to Agricultural Communications Scholarship - Jean A Parrella; Holli R Leggette; Madalynn P Kainer; McKenna L Bush (Journal of Applied Communications, 2023)
Agricultural communications scholars do not use a national research agenda to guide their research, which could be limiting the impact and rigor of the discipline. In this commentary, we argue that agricultural communications scholars should adopt the science communication research agenda published by the National Academies of Sciences, Engineering, and Medicine in 2017 because the goals of science communication, outlined in the agenda, are relevant to agriculture. Members of the committee who developed the agenda study science communication in contexts of food, agriculture, life sciences, the environment, political science, health, nutrition, and psychology, among others. They developed the agenda with the intent for it to inform and guide research in all science communication sub-disciplines or areas involving contentious public issues. We provide examples of studies that have used the agenda to inform research in agricultural and natural resources communications. We also explain how research priorities outlined in the science communication research agenda align with agricultural communications scholarship. Recognizing there are challenges unique to agriculture, we recommend agricultural communications scholars use the science communication research agenda as a research guide and adapt the relevant research recommendations for agricultural communications.
Keywords: agricultural communications; research agenda; science communication